SYSTEMIC-FUNCTIONAL LINGUISTICS IN THE STUDY OF MATHEMATICAL LANGUAGE. SOME CONTRIBUTIONS - López-Acosta, Luis Alberto (2024)
This paper shows some of the possibilities of using Systemic-Functional Linguistics for the study of mathematical language. These possibilities are taken from three investigations that aimed to understand the grammatical and multisemiotic characteristics of different algebraic discourses based on translations of original texts in the history of the development of algebra, as well as student texts when solving problems related to the algebra developed by Viète and Descartes. The results of these studies have shown the grammatical and semantic characteristics that differentiate different types of algebraic texts and others belonging to students. The use of certain mechanisms of intersemiosis between the different semiotic resources of mathematical language: natural language, symbolism and images is also addressed. The main objective is to show how the methods of analysis from this theoretical approach can visualize hidden elements for researchers in Mathematics Education.